Avaliação in vitro do potencial antioxidante de extratos de grão e casca do sorgo granífero [Sorghum bicolor (l.) Moench] híbrido Guanipa 71 - Salazar, Gerson Torres (2016)
Sorghum for presenting a considerable nutritional value is an important animal and human food source in Asia and Africa. Moreover, phenolic compounds present in the pericarp of the grains are recognized as important antioxidants. Considering such properties, this study has been developed to obtain aqueous and acetone/water extracts from the grains and shells of grain sorghum [Sorghum bicolor (L.) Moench] hybrid Guanipa 71, Portuguesa state- Venezuela, in order to investigate its possible antioxidant effects in vitro. Higher extraction yields were obtained with acetone/water 7:3. Indeed, HPLC analysis detected all extracts the chlorogenic, caffeic, gallic, ellagic acids and the flavonoids catechin, rutin, quercitrin, quercetin, and luteolin. The shells and grains acetone/water extracts ECAC – ECAG, inhibited the radical DPPH● with IC50 (μg/mL) of 31.34 and 36.48, also showed the ability to reduce Mo (VI) in the Antioxidant Capacity Relative to the rutin assay (CAR) to IC50 (μg/mL) of 303 and 227.6 respectively. The test of the -phenanthroline the grain and shells aqueous extracts EAG – EAC, exhibited the highest chelating activity of Fe+2 65.09% and 59.12%. However, the ECAG and ECAC extracts exhibited the highest percentages of reducing Fe+3 42.3% and 22.9%, and inhibited the oxidative degradation of 2-deoxyribose in the Fenton reaction, a 17.8% and 29.6%. Together, the results show that extracts exhibited antioxidant potential through electron transfer, radical scavengers and chelating, highlighting the ECAC with the highest potential. Overall, data from this work will contribute to the advancement of research seeking to establish the antioxidant potential of natural in vitro other sorghum hybrids extracts, and in this scenario indicate the relevance of sorghum Guanipa 71 extracts.